Primates 2018
DOI: 10.5772/intechopen.71830
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System in the Vervet Monkey Retina

Abstract: The main active compound found in the marijuana plant, tetrahydrocannabinol, is responsible for its psychotropic effects but also for its numerous beneficial actions such as appetite stimulation, nausea reduction, analgesia, and muscle spasm suppressor. Although cannabis consumption leads to some visual disturbances, the exact role of the endocannabinoid system (ECS) in normal vision is still unknown. Many studies have looked into the localization of this complex system (receptors, ligands, and enzymes) throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Expression studies have shown that CB1R, CB2R, GPR55, and TRPV1 are present in the retina of multiple species [13,14,17,18,[21][22][23][24][25][26], but their differential expression has been found solely in the monkey retina [16,[27][28][29][30]. More precisely, our studies demonstrate that these receptors are distributed in the vertical and horizontal pathways of the vervet monkey retina.…”
Section: The Retinal Endocannabinoid Systemmentioning
confidence: 48%
See 1 more Smart Citation
“…Expression studies have shown that CB1R, CB2R, GPR55, and TRPV1 are present in the retina of multiple species [13,14,17,18,[21][22][23][24][25][26], but their differential expression has been found solely in the monkey retina [16,[27][28][29][30]. More precisely, our studies demonstrate that these receptors are distributed in the vertical and horizontal pathways of the vervet monkey retina.…”
Section: The Retinal Endocannabinoid Systemmentioning
confidence: 48%
“…Similarly, commercially available TRPV1 antibodies generate non-specific labeling in the retina of some species [33]. Using the non-human primate model and antibodies directed against human epitopes for cannabinoid receptors, in our experience, was found adequate [30,34]. In line with this, we compared the alignment of the human sequence for these 4 receptors (Figure 3).…”
Section: The Retinal Endocannabinoid Systemmentioning
confidence: 86%
“…Cannabinoid receptors are localized throughout the retina of several animal species [ 1 , 2 ], including primates [ 3 , 4 , 5 , 6 , 7 ]. In monkeys, the cannabinoid receptor type 1 (CB1R) is mainly expressed in the cones of the central retina [ 8 ], whereas the cannabinoid receptor type 2 (CB2R) is localized in the retinal glia (Müller cells) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Full-field electroretinogram (ffERG) recordings represent a useful clinical tool to evaluate the integrity of the retina. The ffERG is a non-specific mass response made out of several retinal sources that are summed throughout the retina, and this method has been used for studying the eCB system in several animal species including mice and primates [ 1 , 3 , 4 , 14 , 15 , 16 , 17 ]. However, less is known about eCB signaling in cone responses using the photopic flicker ERG, especially in the 30 Hz flicker frequency that is known to activate mainly the cone system [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation